(untitled) (Modern education and development, 2025)
This article analyzes the modern and innovative technologies used in the provision of heat supply in housing. Solar thermal systems, geothermal heating, intelligent control equipment, and the use of energy-efficient insulation materials are considered. Also, the advantages of each technology are explained through technical specifications, performance indicators and performance diagrams. The information in the article is of practical importance in improving heat supply in housing, increasing energy efficiency and protecting the environment.